The use of dietary supplements by athletes - Maughan, R. J.; Depiesse, F.; Geyer, H. (Journal of Sports Sciences, 2007)
Many athletes use dietary supplements as part of their regular training or competition routine, including about 85% of elite track and field athletes. Supplements commonly used include vitamins, minerals, protein, creatine, and various "ergogenic" compounds. These supplements are often used without a full understanding or evaluation of the potential benefits and risks associated with their use, and without consultation with a sports nutrition professional. A few supplements may be helpful to athletes in specific circumstances, especially where food intake or food choice is restricted. Vitamin and mineral supplements should be used only when a food-based solution is not available. Sports drinks, energy bars, and protein - carbohydrate shakes may all be useful and convenient at specific times. There are well-documented roles for creatine, caffeine, and alkalinizing agents in enhancing performance in high-intensity exercise, although much of the evidence does not relate to specific athletic events. There are potential costs associated with all dietary supplements, including the risk of a positive doping result as a consequence of the presence of prohibited substances that are not declared on the label.